Spinning and colour properties of the active asteroid (6478) Gault. Issue 1 (24th January 2020) - Carbognani, Albino; Buzzoni, Alberto
ABSTRACT: We report on accurate BVR c observations of (6478) Gault, a 5–6 km diameter inner main-belt asteroid in the Phocaea family, notable for its sporadic, comet-like ejection of dust. This curious behaviour has been mainly interpreted as reconfigurations after YORP spin-up, although merging of a contact binary system cannot be fully excluded. We collected optical observations along the 2019 March–April period, at orbital phase angles between 12° and 21°, to search for direct evidence of asteroid quick spinning rotation. A prevailing period value of 3.34 ± 0.02 h is supported by our and other photometric observations. In the YORP spin-up hypothesis, this period points to a bulk density ρ ≈ 1 g cm^-3 . The mean colours are B − V = +0.82±0.3, V − R c = +0.28±0.06, and B − R c = +1.11±0.4, but we have observed a trend towards bluer colour during the April session, with about Δ( B − V ) ∼ 0.35 ± 0.09 mag. This colour change can be due to asteroid rotation and support the hypothesis that there is a bluer surface under the Gault's dust.